(untitled) (Experimental biology, 2015)
The obtained results indicate the high efficiency of application the infusion of Vasaprostan (as part of combination treatment) for reduing the grade of multiorgan dysfunction that finally improves the results of surgical treatment. As our researches show the task of prime importance in the complex treatment is the hormone, volemic metabolic disruptions, and accordingly macro- and microcirculatory abnormalities, that is determinative in efficiency of antibacterial therapy, efferent detoxication and prevention of multiorgan inefficiency.